Designing professional career by students – physical education teachers - Starościak , Wojciech; Dębska, Urszula; Guła-Kubiszewska, Halina (Kultura-Społeczeństwo-Edukacja, 2018)
Starościak Wojciech, Dębska Urszula, Guła-Kubiszewska Halina, Designing professional career by students – physical education teachers. „Kultura – Społeczeństwo – Edukacja” nr 2(14) 2018, Poznań 2018, pp. 183–203, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.14. The study identified physical education students’ opinions about and vision of personal career. It was conducted with a questionnaire designed by A. Cybal-Michalska for planning career prospects and career development in modern society by academic youth. Results demonstrate the professional expectations of the sample to be largely met. Students of the University School of Physical Education in Wroclaw are oriented towards individualistic and collectivistic values to a similar extent. Both groups are moderately satisfied with study choices and have a realistic outlook on the difficulties in finding a job consistent with their education. They assess the prospect of a satisfactory career on an equally moderate level, although individualist-oriented students perceive significantly fewer ways of achieving professional success. Collectivistic students emphasize values characteristic of a safe future and working with people and for people. Individualistic students are geared towards innovative and creative activities. Students perceive their careers in the psychological dimension, and select lifestyle and professionalism as the lead guides in career development.